Graham Green: His Vision of Fiction: Exploring Graham Greene's Moral Vision Through His Novels (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Greene's novels are the expression of a variety of experiences of the novelist. These varied experiences have resulted in a moral vision in the novels. Greene is predominantly a religious writer. Therefore, it is obvious that his preoccupation with evil is linked with his religious consciousness. The treatment of evil reminds the reader of the novelist's obsessive awareness of God and his mercy. Greene was not blind to the rampant evil in the society. His early experiences deeply stirred his consciousness. This consciousness of evil finds expression in his major novels, particularly, Brighton Rock, The Power and the Glory and The Heart of the Matter.